Identifying Key Leadership Performance Dimensions for Improving Public Service Quality: Evidence from Family Planning Services in Indonesia - Ade Setiadi (Sultan Publisher, 2023)
Leadership performance has a big influence on the quality of public services provided by government institutions. The objective of this research is to analyze the role of leadership performance and its impact on the quality of public service at the Regional Technical Implementation Unit for Women's Empowerment, Child Protection, Population Control and Family Planning in Bongas District, Indramayu Regency. To study it quantitatively, a descriptive design was used. The data were gathered through questionnaires distributed to 85 respondents and were analysed using descriptive analysis, tests on validity and reliability of the instruments and analysis of relationship between dimensions of leadership performance and quality of public services. The results show that the performance of the leaders was generally rated as good and the evaluations were positive for the dimensions of work planning, implementation of work plans, execution of directives of the organization, quality of work and achievement of targets of the organization. Also, the quality of public services was considered as good, which demonstrates a positive assessment of the services offered by the respondents. The findings indicate the good leadership practices as facilitators of the provision of quality public services and enhancers of the organizational performance. Better planning, implementation, coordination and delivery of organisational goals to build leadership capacity is expected to further improve the effectiveness and responsiveness of public service delivery. The findings offer practical insights for public sector organizations seeking to improve service quality through effective leadership practices.